The impaired gene expression of adenosine monophosphate-activated kinase (AMPK), a key metabolic enzyme in leukocytes of newly diagnosed rheumatoid arthritis patients - Samimi, Zahra; Kardideh, Bahareh; Zafari, Parisa; Bahrehmand, Fariborz; Roghani, Seyed Askar; Taghadosi, Mahdi (Molecular biology reports, 2019)
The disturbed immune homeostasis is involved in the pathogenesis of an array of autoimmune diseases like rheumatoid arthritis (RA). The adenosine monophosphate-activated protein kinase (AMPK) with a pivotal role in immunometabolism process, also plays a regulatory function in the immune system. This study aims to evaluate the alteration of AMPK gene expression in peripheral blood leukocytes of RA patients and its effects on disease severity as well as plasma levels of anti-inflammatory cytokines. 60 RA patients, including 30 newly diagnosed and 30 patients whose disease were under controlled with the combinational disease-modifying anti-rheumatic drug (DMARD), as well as 30 healthy subjects, were enrolled in our study. The gene expression of AMPK was evaluated using real-time PCR method. The plasma concentrations of IL-10 and TGF-β1 were measured using sandwich ELISA. The gene expression of AMPK was significantly lower in the newly diagnosed RA patients in comparison with the control group ( P = 0.049). Inversely, in RA patients who received DMARD therapy, the gene expression of AMPK was significantly higher than the control group ( P = 0.003). There was no significant correlation between AMPK gene expression and plasma levels of IL-10 and TGF-β1. The plasma levels of TGF-β1 was significantly higher in both newly diagnosed and under-treatment patients compared with healthy subjects ( P < 0.001). The impaired gene expression of AMPK in peripheral blood leukocytes and elevated levels of plasma TGF-β1 can be contributed in RA pathogenesis.